Technology Readiness Model (Trm) Dan Technology Acceptance Model (Tam) Dalam Memprediksi Niat Individu Dalam Menggunakan E-Learning - - Rahab; - Haryadi; Hermin Endratno (Conference In Business, Accounting, And Management (CBAM), 2012)
The Internet and Web-based technologies have used to support implementation learning program. E-learning is utilization information technology to support learning activity. Using e-learning in higher education have important role to support learning effectiveness. Some of universities in Indonesia have begun to implement online learning to support learning process. This study investigated the effect of individual readiness on e-learning acceptance. This study combine between technology readiness model with technology acceptance model into one model to investigate the role individual technology readiness to technology acceptance. Individual technology readiness are measured by four dimensions are optimism, innovativeness, insecure, discomfort. An empirical study was conducted among lecturer at JenderalSoedirman University. Partial Least Square was used to analyze the model. This study show that from four dimensions of technology readiness only optimism dimension that effect to perceive ease of use and perceive usefulness.This study also show that intention to use e-learning is effected by their perception to e-learning usefulness.Based on this findings can be concluded that lecture who have higher optimism will have higher perceive ease to use and usefulness of e-learning. Lecture will use e-learning if they perceive that e-learning useful to support learning process.Keywords: Technology Acceptance Model (TAM), Technology Readiness model, E-learning.